Exploring the lived experiences of South Asian international students in Canadian higher education: Implications for social work practice - Karki, Karun Kishor; Bhattarai, Ashmin Hari; Gyan, Charles (Journal of International Students, 2026)
Canada has emerged as a key destination for international students, including a significant population from South Asia. This qualitative study explores the multifaceted experiences of South Asian international students in Canadian higher education from a social work lens. Drawing on semi-structured interviews with seven international students from four South Asian countries (Bangladesh, India, Nepal, and Sri Lanka), this study reveals critical themes, including challenges in cultural adaptation, academic pressures, financial strain, and the ability to navigate support systems. The findings highlight the crucial role of social support networks and culturally informed services in fostering student well-being and academic success. This study urges culturally responsive social work interventions and policy reforms to better support international students, promote their integration, and mitigate potential mental health challenges.